"Frente de Aragón. Grupo de milicianos de Asturias con destino a Zaragoza". Copied from CNT collection - Sagarra, Josep M., (1936)
"Frente de Aragón. Grupo de milicianos de Asturias con destino a Zaragoza". Copied from CNT collection.